Microscopic analysis of overglaze green pigment on Chinese famille rose porcelain from the Imperial Palace. Issue 6 (8th December 2020) - Li, Yuanqiu; Sciau, Philippe; Zhu, Jian; Ji, Luoyuan; Shan, Yingying; Song, Guoding
Abstract: Famille rose porcelain made in the imperial workshop was one of the symbols of the highest manufacturing techniques in ancient China. It was very precious and only owned by the royals for a long time. Because of its complex making technology, overglaze green pigment painted on famille rose porcelain shows many variations. In this work, selected porcelain shards that were excavated at the Forbidden City were analyzed by using microscopy observation, micro‐Raman spectroscopy, scanning electron microscopy, and energy dispersive X‐ray spectrometer to obtain a deep understanding of overglaze green pigment technique on famille rose porcelain. The results revealed that four types of green pigment are used in the selected samples. With different recipes and combinative ways on green pigment and opaque white pigment, craftsmen can choose the using method of pigment to get the effect they want. Abstract : Four kinds of green pigment on Chinese famille rose porcelain have different recipes. Different microstructures are found in green pigments under scanning electron microscopy observation, which indicates different using methods used in famille rose porcelain. The making technology of pigments on famille rose porcelain is sophisticated. Craftsmen, who worked in the imperial workshop, chose different using methods of pigments to get different appearances they want.